2014
DOI: 10.1093/jxb/eru042
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of C4 photosynthesis along a leaf developmental gradient in two Cleome species having different forms of Kranz anatomy

Abstract: SummaryIn Cleome species (Cleomaceae) having two different forms and evolutionary origins of Kranz anatomy there is convergence in the structural and biochemical expression of C4 traits during leaf ontogeny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 62 publications
(148 reference statements)
6
30
0
Order By: Relevance
“…Similar gradients in leaf maturation have recently been reported in both C. gynandra and Cleome angustifolia , and immunolocalisation showed selective localisation of RuBisCO in chloroplasts of the BS prior to structural differentiation of M and BS cells [24]. This suggests in C. gynandra , trans -acting factors which are selectively expressed in M or BS cells, and which appear early in the basal section of the leaf, may be candidates for cell specific control of synthesis of some C 4 enzymes [24], [40]. Equivalent gradients in gene expression are detected along ∼10 cm of maize leaf.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar gradients in leaf maturation have recently been reported in both C. gynandra and Cleome angustifolia , and immunolocalisation showed selective localisation of RuBisCO in chloroplasts of the BS prior to structural differentiation of M and BS cells [24]. This suggests in C. gynandra , trans -acting factors which are selectively expressed in M or BS cells, and which appear early in the basal section of the leaf, may be candidates for cell specific control of synthesis of some C 4 enzymes [24], [40]. Equivalent gradients in gene expression are detected along ∼10 cm of maize leaf.…”
Section: Discussionsupporting
confidence: 84%
“…In maize 21–25% of all genes expressed in leaves were estimated to be differentially expressed in M and BS cells [13], [24]. As these maize experiments were conducted with very different technologies there are significant differences in their estimates of gene expression, however we found 1,154 and 1,429 genes that were preferentially expressed in the M or BS respectively in both maize datasets.…”
Section: Discussionmentioning
confidence: 69%
“…By contrast with grasses, our knowledge on the ontogeny of the bundle sheath in dicots is limited. It has been reported that the bundle sheaths of C 3 and C 4 Cleome species, originate from more than one layer of ground meristem cells and only adaxial bundle sheath cells are of procambial origin (Koteyeva et al ., ). As the bundle sheath and vascular tissue either completely or partially arise from the same cell lineage, changes in the vascular tissue might subsequently result in changes in the bundle sheath anatomy as well.…”
Section: Discussionmentioning
confidence: 97%
“…All forms of C 4 species studied so far have been observed with the gradient differentiation of the photosynthetic structure and biochemistry, which finally results in establishment of a fully functional C 4 syndrome (Koteyeva et al, 2014;Koteyeva et al, 2016). In the Kranz-type C 4 species representatives, maize and Arundinella hirta in the Poaceae, the latter has not only M and BS cells (normal Kranz cells) but also another type of Kranz cells (named as distinctive [D] cells), which are not associated with vascular bundles (VB); however, all cell types show progressive differentiation and enzyme induction pattern, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In coordination with formation of Kranz anatomy, the chloroplast dimorphism and mitochondrial differentiation are established, and the expression of PPDK, NAD-malic enzyme (NAD-ME), RUBPC, or PEPC is significantly increased in parallel (Koteyeva et al, 2011a). Different types of anatomy between Cleome angustifolia and Cleome gynandra (with single and multiple Kranz units, respectively) suggest the independent evolutionary origins of C 4 photosynthesis, but they present similar developmental enhancement of C 4 system (Koteyeva et al, 2014). In SC-C 4 species S. aralocaspica and B. sinuspersici, a gradual enhancement of development along a longitudinal gradient of the young leaf is accompanied by increasing activity of photosynthetic enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%